'Subtle sleights': Metadrama and the informer in Edwards's Damon and Pythias. (November 2017) - Angus, Bill
In early modern England, a proliferation of metadramatic devices coincides with an increasing awareness of the ubiquity of the informer. Richard Edwards's Damon and Pythias (1564) registers forms of oversight associated with informers in its metadramatic structures. 1564 also witnesses an expansion of the Privy Council's anti-recusant policy, and thus the work of informers. The many instances of characters standing aside to observe others suggest that the informer figure both permeates the conditions of early modern dramatic production and haunts the vagaries of reception. Edwards's drama offers a solution to this perceived abuse of authority in the form of classical amity.